Relações de trabalho e a (re)organização do movimento social cineclubista pernambucano - Lima, Rose Kelly Araujo (2023)
This dissertation aims to analyse the working relationships in the organization of the film societies movement in Pernambuco, focusing on the experiences promoted in the Metropolitan Region of Recife (RMR). The work emphasizes the film society experiences that foster exhibition circuits, which use cinema and debate as a specific modality for the critical formation of individuals and collectives. In terms of methodological procedures, this work uses bibliographical and documentary research. To this end, it will seek to combine a historical contextualization of the film society production chain in some different periods in order to indicate the situation of the film societies active at certain times, their activities, their projects, films being shown, aspects of their organization and some of the problems faced by their workers in Pernambuco. Finally, elements of labor legislation will also help to understand the political and economic situation at the time. This dissertation is relevant because of its commitment to problematizing the contradictions surrounding the way in which film society workers act and interact in the work processes to which they are subjected.